Recurrent cardiotoxicity potentiated by the interaction of proteasome inhibitor and immunomodulatory therapy for the treatment of multiple myeloma. (19th October 2017) - Fradley, Michael G.; Groarke, John D.; Laubach, Jacob; Alsina, Melissa; Lenihan, Daniel J.; Cornell, Robert F.; Maglio, Michelle; Shain, Kenneth H.; Richardson, Paul G.; Moslehi, Javid
Summary: Patients with multiple myeloma (MM) have improved treatment options, including immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs). Despite their efficacy, increased rates of cardiovascular (CV) complications occur in patients exposed to some of these therapies. While previous research has focused on identifying the toxicities inherent to each specific agent, the CV side effects may be potentiated by the combination of PIs and IMiDs plus dexamethasone. We present a patient with MM with recurrent cardiotoxicity only when exposed to combination PI and IMiD‐based therapy. We also review the literature in this context, and propose a potential algorithm for cardiotoxicity prevention in this population.